2001
DOI: 10.2166/wst.2001.0304
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of prototype compound parabolic collector-reactors (CPC) on the road to SOLARDETOX technology

Abstract: Solar photocatalytic detoxification of non-biodegradable chlorinated hydrocarbon solvents (NBCS) is carried out in different concentrating and non concentrating devices using TiO2 as a photocatalyst fixed on the inner surface of the reaction tubes or as a slurry catalyst which has to be removed from the treated water. The reaction is most effective using 200 mg/l of TiO2 as a slurry in a non concentrating CPC reactor. The concentrating parabolic trough reactor has a poor activity because of its minor irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Funken et al 108 worked on the solar photocatalytic detoxification of nonbiodegradable chlorinated hydrocarbon solvents (NBCSs) in different concentrating and nonconcentrating devices using TiO 2 as the photocatalyst either fixed on the inner surface of the reaction tubes or in a slurry. They suggested that the reaction was most effective using a TiO 2 concentration of 200 mg/L as a slurry in a compound-parabolic-concentrator reactor.…”
Section: Photocatalytic Reactorsmentioning
confidence: 99%
“…Funken et al 108 worked on the solar photocatalytic detoxification of nonbiodegradable chlorinated hydrocarbon solvents (NBCSs) in different concentrating and nonconcentrating devices using TiO 2 as the photocatalyst either fixed on the inner surface of the reaction tubes or in a slurry. They suggested that the reaction was most effective using a TiO 2 concentration of 200 mg/L as a slurry in a compound-parabolic-concentrator reactor.…”
Section: Photocatalytic Reactorsmentioning
confidence: 99%
“…This reactor is similar to the SOLARDETOX prototypes used at the Plataforma Solar de Almería and the German Aerospace Center, Cologne [38,39], but the mirrors were calculated exclusively for this reactor and the ratio between irradiated surface and dark tubing is higher. Since the BRITE EURAM SOLARDETOX project CPC-type reactors are known as very powerful solar reactors for water treatment up to a pilot plant scale [38,39].…”
Section: Photodegradation Essaysmentioning
confidence: 99%
“…Different solar driven CPC type reactors with 5 l and 60 l volume were used for degradation tests (Funken et al, 2001) as well as UV-lamp driven reactors with a volume of 0.8 l to 5 l and a power consumption between 150 W and 1,000 W. The tests were compared to define advantages and disadvantages of both reactor types especially for the use in a sunny region like Minas Gerais or São Paulo.…”
Section: Methodsmentioning
confidence: 99%